Autocatalytic influence of different levels of arsine on the thermal stability and pyrolysis of polypropylene (2022)
In this article, the pyrolysis and thermo-degradation of 11 virgin-polypropylene (virgin-PP) with different levels of arsenic in its polymer matrix, was carried out in a discontinuous quartz reactor at 500 °C. To quantify arsine (AsH3), 4 points were sampled during the PP synthesis process and a methodology was applied by GC with 4 detectors, which simultaneously and with a single injection allowed to quantify multiple components. AsH3 in propylene varied between 0.05 and 4.73 ppm and arsenic in virgin-PP residues between 0.001 and 4.32 ppm for PP0 and PP10. These generated an increase in the melt flow index from 3.0 to 24.51 and maintained a direct relationship with an R2 of 0.9993. The origin of thermo-oxidative degradation and the beginnings of virgin-PP pyrolysis are explained by the formation to aldehyde, ketone, alcohol, carboxylic acid functional groups, CO and CO2. These species caused TG and DTG curves to have atypical behavior for PP. For example, PP10 with an arsenic content of 4.32 ppm presented 3 degradation peaks at 80, 90 and 200 °C with a mass loss ratio of 22%, 18% and 55% °C−1 respectively. During pyrolysis the highest percentage of alkanes was found in PP0 with an average value of 62.4%, and the lowest values were found in PP8 to PP10, with oscillations between 0% and 1.4%. The total concentration of oxidized species for PP0 to PP10 was 2.26%, 32.7%, 43.1%, 50.9%, 59.3%, 66.2%, 75.0%, 83.0%, 89.1% and 97.5% respectively. In an O2 atmosphere ketones and carboxylic acids were only identified in PP0 to PP5. CO2 concentrations in PP5 to PP10 were of 100%.